Remote Sensing Monitoring of Vegetation Coverage of Hunshandake Sand Based on HJ-1A. Issue 1 (May 2021) - Feng, Tianshi; Wang, Zhiguo; Pang, Zhiguo; Jiang, Wei; Li, Hao
Abstract: Hunshandake Sand has sparse vegetation and serious desertification, which is one of the main reasons for the dust weather in the Beijing-Tianjin-Hebei region. Dynamic monitoring of vegetation coverage in this area is of great significance for predicting sand and dust weather in the Beijing-Tianjin-Hebei region. Remote sensing technology has the advantages of large area, multiple time phases, and high accuracy. This study is based on the CCD data of the HJ-1A, using NDVI parameters as the main input parameters, and using an improved pixel binary model to invert the vegetation coverage of the study area. On this basis, the land use type data is used to extract another vegetation coverage of the study area during the period. The vegetation coverage in different periods of the study area is calculated by band to achieve the purpose of dynamic monitoring. The results show that desertification is common in the northwest of the study area, and the vegetation coverage is becoming lower and lower, while the vegetation coverage in the northeast and south is increasing, and the overall vegetation coverage in the study area is increasing. The experimental results are more consistent with the actual situation, which confirms that the improved pixel binary model has higher accuracy and a certain degree of universality, and the overall desertification control effect of the Hunshandake Sand is better.